2011
DOI: 10.1097/bsd.0b013e3182019f3a
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriologic Culture of Excised Intervertebral Disc From Immunocompetent Patients Undergoing Single Level Primary Lumbar Microdiscectomy

Abstract: Diagnostic level of evidence III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
41
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 29 publications
9
41
1
1
Order By: Relevance
“…The current study confirms the findings of other studies [10,11,[27][28][29] where the microorganism most frequently found in the extruded nucleus material is P. acnes, accounting for approximately 80 % of the positive cases. The predominance of P. acnes might reflect the unusual environment in the disc where the lack of vascularity results in a very low oxygen tension and a low pH which provides ideal conditions for low virulent anaerobic bacteria to grow.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study confirms the findings of other studies [10,11,[27][28][29] where the microorganism most frequently found in the extruded nucleus material is P. acnes, accounting for approximately 80 % of the positive cases. The predominance of P. acnes might reflect the unusual environment in the disc where the lack of vascularity results in a very low oxygen tension and a low pH which provides ideal conditions for low virulent anaerobic bacteria to grow.…”
Section: Discussionsupporting
confidence: 92%
“…In 30 cervical disc herniations they found that 59 % had microorganisms present, 37 % with P. acnes. Agarwal et al [28] similarly cultured material excised from 52 patients treated with a single-level microdiscectomy for lumbar disc herniation. Ten (19 %) of the patients had microorganisms present and in 7 (70 %) of those, P. acnes was the sole microorganism isolated.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors found that disc infection due to P. acnes would initiate sciatica [2] or Modic changes [5] but others did not [24,25]. In this study, we found that the prevalence of sciatica was significantly higher in patients with annular tear than those without annular tear.…”
Section: Discussionsupporting
confidence: 62%
“…There are inconsistent results regarding the association between disc infection and development of symptoms [2,5,24]. Some authors found that disc infection due to P. acnes would initiate sciatica [2] or Modic changes [5] but others did not [24,25].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation